Influence of age, group size and the presence of porcine reproductive and respiratory syndrome virus on the collection of oral fluids. (February 2019) - Graage, Robert; Hennig-Pauka, Isabel; Arbinger, Heidelore; Ritzmann, Mathias; Ladinig, Andrea
Highlights: Oral fluid (OF) was collected by presenting pigs with a rope to chew; 76.5–81.9% pigs chewed the rope. The interaction of pigs with the rope was only influenced by group size. Providing one rope in groups of 20–30 pigs aged 4–14 weeks was sufficient to collect OF samples. There was an almost perfect and significant agreement between OF and serum samples for antibody detection. Abstract: Pen-based oral fluid (OF) samples have been approved for detecting porcine reproductive and respiratory syndrome virus (PRRSV) RNA and antibodies. The aim of the study was to investigate the influence of age, group size and the presence of PRRSV infection on sampling using pen-based OF collected by presenting pigs with a rope to chew. Samples were collected from pigs of 4/5 weeks of age, 7/8 weeks of age and 12/14 weeks of age. Subsequent PRRSV-PCR and ELISA analyses of OF and serum samples were performed. In this study, 76.5–81.9% of pigs chewed the rope. The group size had significant impact on the pig-rope-interaction ( P = 0.047). OF and serum had an almost perfect and significant agreement for the detection of antibodies ( κ = 0.829, P < 0.001) and a fair and not significant agreement ( κ = 0.347, P = 0.75) for the detection PRRSV-genome.